Properties Of Concrete Made Of Ternary Cementitious System - Atur Parhorasan Nusantara Siregar (Jurnal Teknik Sipil, 2018)
AbstractUtilising industrial waste materials containing pozolanic compounds has been widely investigated for cement replacement. Fly ash and microslilica are materials having significant pozolanic compounds and can be used to create ternary cementitious system. Slump of fresh concrete, porosity and compressive strength of hardened concrete were parametric study investigated in this study of ternary cementitious system.  Three types of concrete mixtures, i.e. concrete mixture using original portland cement (OPC) as normal concrete, OPC-fly ash-microslica without superplasticiser, and OPC-fly ash-microslica with additional superplasticiser have been investigated. Fresh concrete using fly ash and microslilica demonstrated having higher slump and lower porosity than normal concrete. Compressive strength of concrete using fly ash and microsilica were higher than normal concrete. Utilising fly ash and microsilica as ternary cementitious system was found to have beneficial effect on fresh concrete, compressive strength and porosity of hardened concrete. AbstrakPemanfaatan limbah industri yang memiliki sifat pozolan banyak digunakan dan dimanfaatkan untuk menggantikan sebagian semen dalam campuran beton. Fly ash dan microsilica merupakan bahan-bahan bersifat pozolan dapat dimanfaatkan dalam membentuk ternary cementitious system. Nilai slump, porositas dan kuat tekan beton menjadi parameter dalam studi ini dalam melihat karakteristik beton yang menggunakan ternary cementitious system berbahan semen, fly ash dan microsilica. Tiga jenis campuran, yaitu campuran normal yang hanya menggunakan semen OPC sebagai bahan pengikat, campuran menggunakan semen OPC-fly ash-microsilica tanpa superplasticiser, dan campuran menggunakan semen OPC-fly ash-microsilica dengan tambahan superplasticiser dibuat untuk dibandingkan karakteristik betonnya. Penggunaan fly ash dan microsilica memperbaiki nilai slump beton segar serta terbukti memperkecil nilai porositas dari beton sehingga kuat tekan beton yang dihasilkan meningkat sejalan dengan uumur beton. Penurunan porositas dan peningkatan kuat tekan beton cukup signifikan dengan penambahan fly ash dan microsilica.